A consideration of certain aspects of South African civil procedural law and civil jurisdiction - Faris, John Andrew (Department of Private Law, 2023)
A salient defect of South African civil procedural law is its lack of a formally recognised fact-discovery mechanism for the purpose of complimenting the process of pre-trial litigation. This defect comes to the fore when the South African discovery model is compared with those of other Anglo-American jurisdictions. In common with other Anglo-American civil procedural systems, South African civil procedural law has formally incorporated within its rules of court a system of discovery, but its discovery model is restricted to that of documentary discovery. 1 In contradistinction with the South African model, the scope of the discovery models of the United Kingdom,2 Austraiia3 and New Zealand4 is far wider in that they include not only documentary discovery but also fact-discovery in the form of interrogatories. The discovery models of the United States5 and Canada6 are even more liberal than the aforementioned because, apart from the practice of documentary discovery and the exchange of interrogatories, oral depositions as a mode of discovery are also permitted. Seen in this context, there is a notional difference between the South African model and the discovery models of other Anglo-American systems in that the latter recognise and apply fact-discovery as a procedure distinct from documentary discovery. Why is this so?